Planning of Interpretation Programs as an Effort to Support Ecotourism Activities at the Wonocolo Teksas Geosite, Bojonegoro Regency - Puguh Andhi Setiawan; Baiquni Baiquni; I Nyoman Sunarta; Heru Suheryadi (Green Publisher Indonesia, 2024)
Geosite Wonocolo Texas is an icon of the Bojonegoro National Geopark, the shallowest traditional oil mine in the world. The purpose of this study was to determine the elements of tourist attractions, determine the characteristics, perceptions, and readiness of the community, determine the characteristics, perceptions, and readiness of managers, determine the characteristics, perceptions, motivations, and preferences of visitors, and determine the interpretation program. This study uses a Mixed Method. In this study, the data analysis used is descriptive qualitative and descriptive quantitative. Data analysis with a qualitative descriptive method is a way of describing data not in the form of numbers but based on comprehensive information obtained in the field and describing the data. This analysis is used to describe the general conditions of the place where the research activities are carried out and the elements of tourist attractions consisting of tourist attractions, accessibility, and amenities. The results of the identification and analysis of the community, managers, and visitors are used as a reference in the interpretation program planning process. The design of the interpretation program planning is in the form of an activity program, interpretation flow, interpretation facilities and infrastructure, and interpretation narratives